Dinamični model nadzora temperature prostora s stropnim hlajenjem - Ćurko, Tonko (Strojniški vestnik, 2000)
This paper presents a dynamic-simulation model of a room's thermal behaviour during summer conditions. Two different systems for the room's temperature control, i.e. ceiling cooling and cold air supply, were analyzed. A comparison of the influencing parameters and the influence on the operating room temperature variation applying both systems are reported.
Keywords: modeli dinamični; temperature sobne; regulacija temperature; hlajenje stropov; dinamični modeli; hlajenje